2022
DOI: 10.1186/s12889-022-14861-8
|View full text |Cite
|
Sign up to set email alerts
|

Minimum dietary diversity and associated factors among children under the age of five attending public health facilities in Wolaita Soddo town, Southern Ethiopia, 2021: a cross-sectional study

Abstract: Background Poor quality diets are the greatest obstacles to survival, growth, development, and learning in children. Dietary diversity is a major problem in developing countries including Ethiopia. For better feeding practices and focused interventions, it is essential to identify dietary diversity in children. In order to draw firm conclusions, previous studies in Ethiopia were unable to get a thorough picture of the dietary diversity among children under the age of five. Therefore, the purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…Poor-quality diets could be the greatest obstacle to children's survival, growth, development, and learning. Dietary diversity is a significant problem in developing countries [39]. This present study showed that MDD was not achieved (87.1%).…”
Section: Discussioncontrasting
confidence: 57%
“…Poor-quality diets could be the greatest obstacle to children's survival, growth, development, and learning. Dietary diversity is a significant problem in developing countries [39]. This present study showed that MDD was not achieved (87.1%).…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies which were conducted to assess dietary diversity among children in Ethiopia investigated the consumption of fruits and vegetables rich in Vitamin A as a single food group, and other fruits and vegetables as another food group and, among other food groups as part of the overall diet. Most of these studies demonstrate low consumption of fruits and vegetables among children age 6-23 months [17][18][19][20][21][22]. For example a study conducted in southern Ethiopia reported 7.2% and 39.1% respectively of children who consumed Vitamin A rich, and other fruits and vegetables the day prior to the survey [18].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal feeding practices were assessed using a threecomponents based system based on WHO/UNICEF recommendations 25,26 . These components included:…”
Section: Assessment Of Maternal Feeding Practicesmentioning
confidence: 99%